(untitled) (Eurasian Scientific Herald, 2026)
This study examines the development of modern transportation systems in the context of Uzbekistan–China cooperation, focusing on infrastructure expansion, technological innovation, and regional integration. The research analyzes how China’s advanced transportation experience, including high-speed rail networks, smart transport systems, and integrated logistics corridors, contributes to the modernization of Uzbekistan’s transport infrastructure. Special attention is given to the Belt and Road Initiative, which plays a key role in strengthening cross-border connectivity and trade efficiency between the two countries. The findings indicate that cooperation with China significantly accelerates Uzbekistan’s transportation system development, improves mobility, and enhances regional economic integration.